The Relapse of Psoriasis: Mechanisms and Mysteries - Danning Tian; Yuping Lai (Elsevier, 2022)
Over the past decades, tremendous success in the treatment of psoriasis has been achieved using biologics, such as neutralizing antibodies against TNF/TNFR, IL-23, and IL-17A/IL-17RA. Although psoriatic skin lesions appear to resolve after treatment with these biologics, lesions often recur after therapy is discontinued or during therapy. Memory T cells residing in the skin have been considered as the major driver of psoriasis relapse. However, whether structural cells in the skin such as keratinocytes and fibroblasts are involved in the relapse of psoriasis is unknown. In this review, we outline the therapeutic rationale of biologics used in the treatment of psoriasis, summarize different clinical features of psoriasis relapse on the basis of preclinical and clinical data, and specifically discuss how memory T cells and structural cells in the skin are involved in psoriasis relapse. Finally, we discuss the future challenges in the basic or clinical research on psoriasis.